2021
DOI: 10.1021/acs.jnatprod.0c01111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Elucidation, Semi-Synthesis, and Structural Modification of C19-Diterpenoid Alkaloids from Aconitum apetalum and Their Neuroprotective Activities

Abstract: Five new aconitine-type C 19 -diterpenoid alkaloids, apetalrines A−E (1−5), were isolated from Aconitum apetalum. Their structures were determined by analysis of 1D and 2D NMR, IR, and HRESIMS data. Semisynthesis of apetalrine B (2) from its parent compound aconorine was achieved to confirm the structure proposed. Twenty derivatives of 2 (11a−11l, 12a, 12b, 12d, 12e, 12j, 12k, 12m, 12n) were synthesized via a unified approach relying on simple coupling reactions. The evaluation of neuroprotective effects of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…83 The latter afforded 5 apetalrines A–E based on N -acylated 2-aminobenzoyl esters and also structurally identified following detailed spectral analysis. 84 Ablajan et al reported 5 previously undescribed DA, barpuberudine and barpubesines A–D, and two interesting novel C18 NDA, barpubenines A–B, isolated from the whole plant of A. barbatum var. puberulum Ledeb.…”
Section: Analysis Of Ndamentioning
confidence: 99%
“…83 The latter afforded 5 apetalrines A–E based on N -acylated 2-aminobenzoyl esters and also structurally identified following detailed spectral analysis. 84 Ablajan et al reported 5 previously undescribed DA, barpuberudine and barpubesines A–D, and two interesting novel C18 NDA, barpubenines A–B, isolated from the whole plant of A. barbatum var. puberulum Ledeb.…”
Section: Analysis Of Ndamentioning
confidence: 99%
“…Nominine showed potent protective activity against MPP + ‐induced apoptosis in SH‐SY5Y cells [9] . Also, apetalrine B, an aconitine‐type C 19 ‐diterpenoid alkaloid isolated from A. apetalum , exhibited good neuroprotective effects in H 2 O 2 ‐treated SH‐SY5Y cells [10] …”
Section: Introductionmentioning
confidence: 99%
“…[9] Also, apetalrine B, an aconitine-type C 19 -diterpenoid alkaloid isolated from A. apetalum, exhibited good neuroprotective effects in H 2 O 2 -treated SH-SY5Y cells. [10] Aconitum leucostomum Worosch. (Ranunculaceae), which grows at altitudes 1400 -2550 m, is a perennial herb distributed in the Gansu province and Xinjiang Uygur Autonomous Region of China.…”
Section: Introductionmentioning
confidence: 99%
“…1) This kind of compounds have attracted considerable interest because of their complex structure, and noteworthy physiological effects. 2) As our ongoing interest in the phytochemical studies on the pharmacologically interesting plants Aconitum and Delphinium, we obtained a series of structurally and chemotaxonomically interesting diterpenoid alkaloids. [3][4][5][6][7] The plant Aconitum novoluridum Munz belongs to the Aconitum genus in the family of Ranunculaceae and is distributed in the northeast of Tibet in China, Bhutan, Nepal, and Sikkim at an attitude of 3800-4500 m. 8) Aconitum novoluridum is similar to Aconitum apetalum, but the stem is lower and thinner, the leaves are smaller, the bracteoles are ovate, the sepals are purplish-red, and the petals are distinguished by short spines.…”
Section: Introductionmentioning
confidence: 99%